Development of Novel Catalyst for the production of sio-Diesel from crude palm oil. - Lee, Keat Teong; Mohamed, Abdul Rahman; Bhatia, Subhash (Universiti Sains Malaysia, 2008)
Production of biodiesel has become popular nowadays as a result of increasing demand for a clean, safe and renewable energy. Biodiesel is made from natural renewable sources such as vegetable oils and animal fats.